Occurrence and potential activity of denitrifiers and methanogens in groundwater at 140 m depth in Pliocene diatomaceous mudstone of northern Japan. Issue 3 (30th July 2013) - Katsuyama, Chie; Nashimoto, Hiroaki; Nagaosa, Kazuyo; Ishibashi, Tomotaka; Furuta, Kazuki; Kinoshita, Takeshi; Yoshikawa, Hideki; Aoki, Kazuhiro; Asano, Takahiro; Sasaki, Yoshito; Sohrin, Rumi; Komatsu, Daisuke D.; et al.
Abstract: Anaerobic microbial activity has a major influence on the subsurface environment. We investigated the denitrification and methanogenesis in anoxic groundwater at a depth of 140 m in two boreholes drilled in a sedimentary geological setting, where the redox potential fluctuated. The average maximum potential denitrification rates, measured under anaerobic conditions in the two boreholes using an 15 N tracer, were 0.060 and 0.085 nmol 30 N2  mL −1  h −1 . The deduced NirS amino acid sequences obtained from in situ samples were similar to those of isolates belonging to the α ‐, β ‐, and γ ‐ Proteobacteria, and the Firmicutes (72–100% similarity). Based on the nirS gene, the same operational taxonomic unit dominated incubated samples from each borehole. Methanogenesis candidates were detected by 16S rRNA gene analysis, but no sequence was detected using primers for the functional methanogenesis gene mcrA . Although the stable isotope signatures suggested that some of the dissolved methane was of biogenic origin, no potential for methane production was evident during the incubations. The groundwater at 140 m depth did not contain oxygen, had an Eh ranging from −144 to 6.8 mV, and was found to be a potential field for denitrification.